Analytical Study of the Penetration of Long Rod Projectiles with Conical and Blunt Nose in Normal and Oblique Ceramic Targets - Salimi , Bahman; Vahedi , Khodadad; Moslemi Petrudi, Amin; Rahmani, Masoud; Cristian Scurtu , Ionut (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The Mechanics of penetration investigate the interactions between projectiles and targets. The Mechanics of penetration were initially developed with military motives and were used in the design and manufacture of durable military vehicles, warships, protective vests, bulletproof panels, satellite protective equipment, nuclear reactor protection used. In this paper, the penetration of cylindrical and conical-nosed long rods projectiles in normal and the diagonally ceramic target is studied by analytically and numerical methods; And the Interface defeat e phenomenon, in which the projectile is eroded so that the material in the target surface is radial and outward flow. A comparison was also made between the oblique and normal penetration of long rods cylindrical and conical-nosed projectiles, which illustrates the importance of collision angles. The analytical relations related to the reduction of velocity and erosion of the projectile mass were investigated concerning the extraction time and kinetic energy loss of the projectile. Transition from the interface defeat phase to the penetration phase is also described in detail, and the variation of the critical speed suffering from the change in the angle of impact has been investigated. Each of the results of the analytical work and numerical simulations has been evaluated by experimental work carried out in previous studies and the comparison of the results shows the acceptable accuracy for the obtained relationships.